Place of judiciary the separation of powers in Russian - N I Yaroshenko (RUDN Journal of Law, 2010)
The article is dedicated to the principle of division of powers and a special place of the judiciary in Russia. The research is based on an analysis of scientific works of Russian and foreign authors, legislation and legal positions of the Constitutional Court of Russia.